2015
DOI: 10.1590/0103-8478cr20140175
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol extract of Cymbopogon winterianus on mortality and number of eggs of Tetranychus urticae

Abstract: Plant extracts have been studied as a promising source of natural insecticides. This study assessed the effect of the ethanol extract of Cymbopogon winterianus

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Further purification of Cymbopogon oil and separation of its active ingredients may enhance its varroacidal effect. In previous studies, Cymbopogon oil has been found to have miticidal activity [26] and it is known that citral, its main component, may kill Varroa mites [41]. However, this is the first study to demonstrate its varroacidal activity and low toxicity to adult bees and larvae.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Further purification of Cymbopogon oil and separation of its active ingredients may enhance its varroacidal effect. In previous studies, Cymbopogon oil has been found to have miticidal activity [26] and it is known that citral, its main component, may kill Varroa mites [41]. However, this is the first study to demonstrate its varroacidal activity and low toxicity to adult bees and larvae.…”
Section: Discussionmentioning
confidence: 86%
“…For example, anethole has shown toxicity to several insects [21,22], nematodes [23], and mites [24]. Cymbopogon oil can kill mosquitoes [25] and mites [26]. Tagetes oil has evidenced pesticide activity against insects such as bedbugs [27] and against ticks [28].…”
Section: Introductionmentioning
confidence: 99%
“…The research on the use of C. winterianus the fields of pharmacology, perfume, aromatherapy, and insect repellent has been widely studied, but the use of C. winterianus in biopesticides is still limited to be studied, especially as a biofungicide agent. Previous studies have reported that essential oil C. winterianus has insecticidal activity against Frankliniella schultzei and Myzus persicae ) and ethanol extract from C. winterianus are insecticidal to Tetranychus urtica (VicentiniI et al 2015). In Thailand, the mixture of crude extract of leaves of C. winterianus and Azadirachta indica A.H.L.…”
Section: Resultsmentioning
confidence: 99%
“…Herbicide effect; phytopathogenic organisms; resistance induction; insects; mites. CHAND et al, 2016;PEREIRA et al, 2012;REHMAN et al, 2019;NGUEFACK et al, 2013;VICENTINI et al, 2015;MANDIRIZA;AVELI, 2018. Lippia sp. Herbicide effect; insects; phytopathogenic organisms.…”
Section: Developmentmentioning
confidence: 99%